2010
DOI: 10.1080/15567030802606228
|View full text |Cite
|
Sign up to set email alerts
|

Photogalvanic Cells as a Device for Solar Energy Conversion and Storage: An EDTA-New Methylene Blue and Safranine O System

Abstract: Photogalvanic effect was studied in photogalvanic cells containing EDTA as reductant, new methylene blue, and safranine O as photosensitizer. The photopotential and photocurrent generated were 740 mV and 110 A, respectively. The observed conversion efficiency was 0.4442% and the maximum output (power) of cell was 81.4 W. The photogalvanic cell can be used for 95 min in the dark due to the storage capacity of the cell. The effects of various parameters on the electrical output of the cell were observed. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Conventionally, the H-shaped glass tubes have been used to fabricate the PG cell. 59,60 But, the recent study reported by Koli et al on Congo Red dye sensitizer (MW 696.66, a diazo dye with −SO 2 O − Na þ and −NH 2 groups) has shown that the use of simple cylindrical glass vessels is not only cheap but also more efficacious in power generation. 44 In present study, the authors have also used simple cylindrical glass vessel for fabrication of the cell based on TPO dye sensitizer (MW 316.27, azo dye with −SO 2 O − Na þ and −OH groups), and have observed enhanced electrical output consistent with the reported study.…”
Section: Comparison Of Results Of the Tpo Dye Sensitizer With Similar...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, the H-shaped glass tubes have been used to fabricate the PG cell. 59,60 But, the recent study reported by Koli et al on Congo Red dye sensitizer (MW 696.66, a diazo dye with −SO 2 O − Na þ and −NH 2 groups) has shown that the use of simple cylindrical glass vessels is not only cheap but also more efficacious in power generation. 44 In present study, the authors have also used simple cylindrical glass vessel for fabrication of the cell based on TPO dye sensitizer (MW 316.27, azo dye with −SO 2 O − Na þ and −OH groups), and have observed enhanced electrical output consistent with the reported study.…”
Section: Comparison Of Results Of the Tpo Dye Sensitizer With Similar...mentioning
confidence: 99%
“…Conventionally, the H‐shaped glass tubes have been used to fabricate the PG cell 59,60 . But, the recent study reported by Koli et al.…”
Section: Comparison Of Results Of the Tpo Dye Sensitizer With Similar...mentioning
confidence: 99%
“…The mixed surfactant base results are reported for better electrical output by Lal and Gangotri 9 . Later on Meena et al, observed the photochemical degradation of dye 10 , Yadav et al, studied photo reduction of methylene blue and Safranine O in EDTA 11 . Rathore et al, 12,13 the shortlived processes in PG cells for solar power generation and storage.…”
Section: Introductionmentioning
confidence: 99%
“…The endeavor to continuously improve and optimize photogalvanic cell by using different dye sensitizers, reductants, and surfactants has been a consistent effort by researchers. Various dye photo‐sensitizers (such as the Bromophenol Red, 3 Congo Red, 4 Azur B, 5 Methylene Blue, 6 Brilliant Cresyl Blue, 7 Rose Bengal, 8 Safranine O, 9,10 Indigo Carmine, 11 Sudan‐I, 12 Rhodamine B, 7 Fast Green FCF, 13 Metanil Yellow, 14 mixed dyes, 15 Eosin, 16 Toluidine blue, 17 etc.) and similarly different reductants (like ethylenediamine tetra acetic acid, 5,6 formic acid, 11 fructose, 12 Fe +2 , 18 sugars, 16 D‐Xylose, 17 etc.)…”
Section: Introductionmentioning
confidence: 99%